Covid-19 Pandemic and its Impact on Orthodontic Patients in Lahore, Pakistan - Aaisha Akbar, Mariam Fatima, Umer Farooq, Kashif Haroon, Junaid Israr, Ghulam Mustafa (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To determine the effect COVID-19 pandemic had on orthodontic patients during the lockdown phase as well as to determine the knowledge of patients regarding the COID-19 disease, its spread, its symptoms, and its prevention. Methodology: This was a cross-sectional descriptive study. It was carried out by distributing a self-administered questionnaire to 300 patients undergoing orthodontic treatment via electronic mail and whatsapp platfortm. The questionnaire assessed the knowledge of the patient regarding the COVID-19 disease, the impact it had on their orthodontic treatment, and their perception of risk and their attitude towards the COVID-19 disease. Results: 274 out of 300 patients responded to our questionnaires; Out of them 73% were females and 47.3% were males. A large number of patients were able to correctly identify the cause, spread, symptoms, and necessary measures needed to be taken to contain the disease. Although majority of the patients considered COVID-19 to be severely dangerous and felt highly vulnerable to the disease; 54.5% were still willing to continue their treatment during the pandemic. The main reason for their willingness was the fear of increased missed appointments leading to increase in treatment time and cost. Conclusions: The pandemic has had an adverse impact on orthodontic treatment regardless. Nevertheless, patients were still inclined to continue their treatment with appropriate infection control and precautionary measures observed both by the patients themselves and the orthodontic clinical staff. Keywords: COVID-19, Health knowledge, Attitude, Practice, Pandemic